Novel water treatment system in a low-resource community. (3rd May 2022) - Nogueira, R. C.; Nigro, M.; Veuthey, J.; Thior, M. D. F; Amour, C. O. D.; Voillat, J.
Abstract: This paper evaluates the performance of a low-cost technology in rural Benin (West Africa) that locally produces chlorine (sodium hypochlorite) and then injects it into the community water tanks. Thirty-one water tanks were selected in cooperation with local authorities to receive electro-chlorinator devices (WATA™). Water samples were tested at two points: before chlorination and at the most distant terminal after chlorination. Residual chlorine control tests and microbiology control tests were performed. Water samples that tested positive for the presence of microorganisms were analyzed at a laboratory when possible. The water provided to the community was not always chlorinated, and over half of the tanks lacked access to chlorine powder. Among the sites using the technology, 30% (9/31) of them had structural problems that prevented the existing system from performing adequately. Furthermore, 60% of the water samples collected before chlorination were positive for microbiological contamination. All samples collected from systems where proper chlorination was taking place tested negative for microbiological contamination. However, the water from six tanks presenting structural problems continued to be distributed to the population despite contamination. The average residual chlorine level analyzed at the most distant terminal fountain was 0.29±0.2 mg/L, which is within the country's reference level 0.1–0.8 mg/L. The installation of water-chlorinator devices (WATA™) produces water without microbiological contamination and with chlorine levels within the WHO's recommended values. However, the success of the technology depends on the pre-existing structure of the water tank. HIGHLIGHTS: Chlorine powder shortage was experienced by 52% of the 31 tanks studied. 60% of water samples collected before chlorination had microbiological contamination. After installation, the average residual chlorine level was 0.29±0.2 mg/L. Infrastructural problems were present in 30% (9/31) of sites. Graphical Abstract